2014
DOI: 10.1371/journal.pone.0115211
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Death during Tuberculosis Treatment of Patients Co-Infected with HIV at the Yaoundé Central Hospital, Cameroon: An 8-Year Hospital-Based Retrospective Cohort Study (2006–2013)

Abstract: BackgroundContributors to fatal outcomes in TB/HIV co-infected patients actively undergoing TB treatment are poorly characterized. The aim was to assess factors associated with death in TB/HIV co-infected patients during the initial 6 months of TB treatment.MethodsWe conducted a hospital-based retrospective cohort study from January 2006 to December 2013 at the Yaoundé Central Hospital, Cameroon. We reviewed medical records to identify hospitalized co-infected TB/HIV patients aged 15 years and older. Death was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
27
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 29 publications
12
27
2
5
Order By: Relevance
“…Similar findings by Agbor et al [14] showed that those who were HIV coinfected and not receiving antiretroviral therapy were more than twofold likely to die. Among those HIV-infected, starting ART in the intensive phase of TB treatment was also associated with lower mortality compared to those who were previously on ART.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar findings by Agbor et al [14] showed that those who were HIV coinfected and not receiving antiretroviral therapy were more than twofold likely to die. Among those HIV-infected, starting ART in the intensive phase of TB treatment was also associated with lower mortality compared to those who were previously on ART.…”
Section: Discussionsupporting
confidence: 86%
“…Being HIV-positive was the most common risk factor for mortality whilst on anti-TB treatment and this has been reported in studies from different parts of the world such as in Cameroon [14], the United States [15], South Africa [16], and Ghana [17]. HIV-positive individuals with latent TB are known to be approximately 20–30 times more likely to develop TB disease than those who are HIV negative, at a rate of 8–10% per year [1], because of their suppressed immune system which can result in an increase odds of mortality with further progression of the HIV disease killing 1 in 3 patients [18].…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of TB patient LTFU recorded at health centers was lower when compared to finding from Morocco [28]. However, it was higher when compared to studies conducted across different parts of the world which includes Ethiopia [1], Ukraine [29], Ethiopia [30,31], Dangila, Ethiopia [32], Cameroon [33], and South Africa [34]. The explanation for the variation could be explained from study setting and sample size.…”
Section: Discussionmentioning
confidence: 78%
“…(4) According to the national annual performance report of Ethiopia, 70% of TB patients with HIV were put on ART (5), but the mortality in TB/HIV co-infected patients remains high even after starting ART. Several factors have been identified that contribute to the high mortality rate, including low baseline CD4 count, having advanced disease at start of treatment and not receiving treatment(6). Most previous studies addressing TB related HIV deaths have focused only on assessing the relative contribution of TB to HIV related mortality.…”
Section: Introductionmentioning
confidence: 99%